Qualidade higiênico-sanitária e ocorrência de Aeromonas sp. e Escherichia coli em tilápias comercializadas no varejo - Barbosa, Mayhara Martins Cordeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Aquaculture development contributed to increase the fish supply at retail. However, this product requires attention to avoid contamination by microorganisms. The objective of this research was to identify microorganisms that indicate hygienic (Staphylococcus coagulase positive and Salmonella sp.) and sanitary (total coliforms, fecal coliforms and Staphylococcus sp.) quality in tilapia that were sold at retail. In addition, it was verified the occurrence of pathogenic Escherichia coli and Aeromonas sp. the sample included tilapia fillets and in natura that was obtained from ten establishments in São Paulo State, Brazil. For the characterization of pathogenic Escherichia coli, the genes stx1, stx2, eae, eltB, estB, estA, aggR and aafll were studied. In addition, the isolates obtained from Aeromonas sp. and Escherichia coli were tested for antimicrobial susceptibility. The results for Salmonella sp. and Staphylococcus coagulase positive were in accordance with Brazilian regulation. However, we found high populations of Aeromonas sp., total and fecal coliforms. The sample allowed to obtain 216 Escherichia coli strains and 96 Aeromonas sp. strains. Five Escherichia coli strains presented genes that were virulence factors coders (eae and estA). Compared to isolates of Aeromonas spp., the most frequent species were Aeromonas trota (50%), Aeromonas veronii biovar sobria (28%) and Aeromonas schubertii (17%). In general, higher frequency of resistant isolates was observed in antimicrobials ampicillin 10?g, amoxicillin + clavulanic acid 20?g, cephalothin 30?g, cefoxitin 30?g, cefuroxime 30?g and cotrimozaxol 25?g. Moreover, it was possible to observe multiple resistance among isolates. In conclusion, the maintenance of health and hygiene practices both in aquaculture and fish sales is necessary because the presence of pathogenic microorganisms with multiple resistances to antimicrobials tested

O desenvolvimento da aquicultura ocasionou o aumento da oferta do pescado em comércios varejistas. Entretanto, esse produto requer atenção para que não ocorra contaminação por microrganismos. Assim, o objetivo desta pesquisa foi identificar microrganismos indicadores de qualidade sanitária (Staphylococcus coagulase positivos e Salmonella sp.) e qualidade higiênica (coliformes totais, coliformes termotolerantes e Staphylococcus sp.) em tilápias comercializadas no varejo, além de verificar a ocorrência de Escherichia coli patogênica e Aeromonas sp. Para isso, a colheita da tilápia, na forma de filé e in natura, foi realizada em dez estabelecimentos de municípios da região Nordeste do Estado de São Paulo. Para a caracterização da Escherichia coli patogênica, os genes pesquisados foram: stx1, stx2, eae, eltB, estA, estB, aggR e aafll por PCR multiplex. Além disso, os isolados obtidos de Aeromonas sp. e Escherichia coli foram submetidos ao teste de susceptibilidade a antimicrobianos. Os resultados para Salmonella sp. e Staphylococcus coagulase positivos estiveram de acordo com a legislação brasileira. Entretanto, foram encontradas altas populações de Aeromonas sp., coliformes totais e termotolerantes. A partir das amostras, foi possível obter 216 isolados de Escherichia coli e 96 isolados de Aeromonas sp. Cinco isolados de Escherichia coli apresentaram genes codificadores de fatores de virulência (estA e eae). Em relação aos isolados de Aeromonas sp., as espécies mais frequentes foram Aeromonas trota (50%), Aeromonas veronii biovar sobria (28%) e Aeromonas schubertii (17%). De forma geral, as maiores frequências de isolados resistentes foram observadas para os antimicrobianos ampicilina 10?g, amoxicilina + ácido clavulânico 20?g, cefalotina 30?g, cefoxitina 30?g, cefuroxima 30?g e cotrimozaxol 25?g. Além disso, foi possível observar múltipla resistência entre ...
Keywords: Peixe; Tilapia (Peixe); Estafilococos; Pescados - Contaminação; Qualidade dos produtos; Fishes